Registro de forésia de ovos de Dermatobia hominis (L.) (Diptera, Oestridae) por Fannia canicularis (L.) e Fannia punctipennis (Albuquerque) (Diptera, Fanniidae) em São Paulo, Brasil - Maia, Bárbara Maria Cerqueira; Prado, Aline Marrara; Purgato, Natane Cássia Sibon; Mira, Cauê Trani; Thyssen, Patricia Jacqueline (EntomoBrasilis, 2018)
Resumo Esta é a primeira vez que se registra a veiculação de ovos de Dermatobia hominis (L.) (Insecta, Diptera, Oestridae) por Fannia punctipennis (Albuquerque) (para o Sudeste do Brasil) e por Fannia canicularis (L.) (para a América do Sul) (Insecta, Diptera, Fanniidae), respectivamente. Phoresy record of Dermatobia hominis (L.) (Diptera, Oestridae) eggs by Fannia canicularis (L.) and Fannia punctipennis (Albuquerque)(Diptera, Fanniidae) in São Paulo, Brazil Abstract This is the first record of Dermatobia hominis (L.) (Insecta, Diptera, Oestridae) eggs carried by Fannia punctipennis (Albuquerque) (for Southeast Brazil) and by Fannia canicularis (L.) (for South America) (Insecta, Diptera, Fanniidae), respectively.